Thomas Jefferson - Burns, Ken, 1953-; Waterston, Sam.; Davis, Ossie; Ward, Geoffrey C.; WETA-TV (Television station : Washington, D.C.); Florentine Films; American Lives Film Project; PBS Home Video ([Alexandria, VA] : PBS Home Video, 2004)
Examines the life of Thomas Jefferson, third President of the United States and author of the Declaration of Independence.
DVD; full screen presentation; Dolby surround stereo.
Closed captioned.
Narrator: Ossie Davis; voices: Sam Waterston, Philip Bosco, Blythe Danner, Amy Madigan, Michael Potts.
Editors, Paul Barnes, Kevin Kertscher ; cinematography, Allen Moore ... [et al].
MPAA rating: Not rated.
Special features: Ken Burns, making history -- A conversation with Ken Burns.
Keywords: Jefferson, Thomas, -- 1743-1826.; Presidents -- United States -- Biography; Biographical television programs; Video recordings for hard of hearing people